Energy Interplay in Materials: Unlocking Next‐Generation Synchronous Multisource Energy Conversion with Layered 2D Crystals. Issue 36 (2nd August 2022) - Corletto, Alexander; Ellis, Amanda V.; Shepelin, Nick A.; Fronzi, Marco; Winkler, David A.; Shapter, Joseph G.; Sherrell, Peter C.
Abstract: Layered 2D crystals have unique properties and rich chemical and electronic diversity, with over 6000 2D crystals known and, in principle, millions of different stacked hybrid 2D crystals accessible. This diversity provides unique combinations of properties that can profoundly affect the future of energy conversion and harvesting devices. Notably, this includes catalysts, photovoltaics, superconductors, solar‐fuel generators, and piezoelectric devices that will receive broad commercial uptake in the near future. However, the unique properties of layered 2D crystals are not limited to individual applications and they can achieve exceptional performance in multiple energy conversion applications synchronously. This synchronous multisource energy conversion (SMEC) has yet to be fully realized but offers a real game‐changer in how devices will be produced and utilized in the future. This perspective highlights the energy interplay in materials and its impact on energy conversion, how SMEC devices can be realized, particularly through layered 2D crystals, and provides a vision of the future of effective environmental energy harvesting devices with layered 2D crystals. Abstract : Layered 2D crystals are exemplar energy conversion materials, able to convert light, heat, or motion to electricity. These energy conversion processes can also occur synchronously, leading to complex energy interplay networks during energy harvesting/transducing. This synchronous multisource energy conversion needs to be studied and understood to enable the fabrication of next‐generation energy harvesting and conversion systems.